Frontiers: Authority, Precarity and Insurgency at the Edge of the State - Michael J Watts (L'Espace Politique)
Two home-grown insurgencies  arose in Nigeria after the return to civilian rule in 1999: Boko Haram in the Muslim northeast, the Movement for the Emancipation of the Niger Delta (MEND) in the oil producing and Christian southeast. The two insurgencies arose, I argue, from frontier spaces in which the limits of state authority and legitimacy intersected with a profound crisis of authority and rule on the one hand, and the political economy of radical precarity on the other. Boko Haram and MEND share family resemblances—they are products of the same orderings of power—despite the obvious fact that one is draped in the language of religion and restoration (but as we shall see modernity) and the insistence that Nigeria should become transformed into a true Islamic state, while the other is secular and civic (and also modern) wishing to expand the boundaries of citizenship through a new sort of federalism. There are striking commonalities in the social composition of the armed groups and their internal dynamics; each is deposited at the nexus of the failure of local government, customary institutions, and the security forces (the police and the military task forces in particular). Each, nevertheless, is site specific; a cultural articulation of dispossession politics rooted in regional traditions of warfare, in particular systems of religiosity, and very different sorts of social structure and identity, and very different ecologies (the semi arid savannas of the north, and the creeks and forest of the Niger delta). In both cases state coercion and despotism and the ethico-moral decrepitude of the state figures centrally as does the politics of resentment that each condition generates among a large, alienated but geographically rooted group of precarious classes.